Respon Pertumbuhan dan Hasil Tanaman Kacang Merah Besar (Vigna angularis) pada Pemberian Pupuk Kandang Kambing dan Pupuk Urea - Ferdinandus Amsul; Zamroni; Darnawi (JURNAL ILMIAH AGROUST, 2022)
The aim of this study was to determine the growth response and yield of large red bean (Vigna angularis L) when given goat manure and urea fertilizer. It has been carried out in Dagaran Hamlet, Kel. Palbapang, Kec. Bantul, Kab. Bantul, Yogyakarta, with an altitude of 50-100 meters above sea level (asl), average rainfall of 1,654 mm/year with an average temperature of 30 ºC. From May to July 2022. The study used a Randomized Block Design (RBD), with 2 treatment factors and 3 blocks. The first factor is the dose of goat manure consisting of 3 levels, namely K1: 5 tons/ha, K2: 10 tons/ha, K3: 15 tons/ha and the second factor is the dose of urea fertilizer consisting of 3 levels, namely D1: 100 kg/ha, D2: 150 kg/ha, D3: 200 kg/ha. Variables observed included: plant height, number of leaves, plant fresh weight, plant dry weight, number of pods per plant, fresh weight of pods per plant, dry weight of pods per plant, dry seed weight per plant, number of seeds per plant, weight of 100 seeds and seed weight per hectare. Data analysis using variance, for significantly different treatments was tested with the least significant difference test (LSD) at the 5% level. Based on the results of variance, there was no interaction between the treatment of goat manure doses and urea fertilizer doses on the observation variables of plant height, number of leaves, number of pods per plant, fresh weight of pods per plant, dry weight of pods per plant, dry seed weight per plant, and number of seeds per plant. The interaction between the doses of goat manure and the dose of urea fertilizer was found in plant fresh weight, plant dry weight, weight of 100 seeds, and seed weight per hectare. The highest growth in plant dry weight was obtained in the K2D1 treatment which was not significantly different from K1D2, K2D2, K3D2, K1D3, and K3D3. The highest red bean yield (tonnes/ha) was obtained in the D3K1 treatment which was not significantly different from K2D1, K3D1, K3D2, and K3D3.